Rhoifolin Alleviates Alcoholic Liver Disease In Vivo and In Vitro via Inhibition of the TLR4/NF-κB Signaling Pathway - Mai, Baoyu; Han, Ling; Zhong, Jiarui; Shu, Jingqi; Cao, Zelin; Fang, Jiaqi; Zhang, Xiaoying; Gao, Zelin; Xiao, Fengxia (Frontiers in Pharmacology, 2022)
Background: Alcoholic liver disease (ALD) is a common chronic liver disorder worldwide, which is detrimental to human health. A preliminary study showed that the total flavonoids within Citrus grandis ‘Tomentosa’ exerted a remarkable effect on the treatment of experimental ALD. However, the active substances of Citrus grandis ‘Tomentosa’ were not elucidated. Rhoifolin (ROF) is a flavonoid component with high content. Therefore, this research aimed to evaluate the hepatoprotective effects of ROF and its possible mechanisms. Methods: Molecular docking was performed to analyze the binding energy of ROF to the main target proteins related to ALD. Subsequently, mice were fed ethanol (ETH) for 49 days to establish the chronic alcoholic liver injury models. The liver pathological injury, serum aminotransferase levels, and oxidative stress levels in the liver tissue were measured. Human normal hepatocytes (LO2 cells) were incubated with ETH to construct the alcoholic liver cell model. The inflammatory markers and apoptosis factors were evaluated using real-time PCR and flow cytometry. Finally, the effects of ROF on the CYP2E1 and NF-κB signaling pathway were tested in vitro and in vivo. Results: Molecular docking results demonstrated that ROF was able to successfully dock with the target proteins associated with ALD. In animal studies, ROF attenuated ETH-induced liver damage in mice through decreasing the serum concentrations of AST and ALT, reducing the expression of inflammatory cytokines and maintaining antioxidant balance in the liver tissue. The in vitro experiments demonstrated that ROF suppressed ETH-induced apoptosis in LO2 cells by promoting Bcl-2 mRNA, inhibiting Bax mRNA and Caspase3 protein expression. ROF decreased the content of LDH, ALT, AST, ROS and MDA in the supernatant, induced the activity of GSH and SOD, and inhibited TNF-α, IL-6 and IL-1β expression levels. Mechanistically, ROF could significantly downregulate the expression levels of CYP2E1, TLR4 and NF-κB phosphorylation. Conclusion: This study indicates that ROF is the active component within the total flavonoids, which may alleviate ETH-induced liver injury by inhibiting NF-κB phosphorylation. Therefore, ROF may serve as a promising compound for treating ALD.